Occurrence and Antimicrobial Resistance of Arcobacter spp. Recovered from Aquatic Environments - Sonia Sciortino; Pietro Arculeo; Vincenzina Alio; Cinzia Cardamone; Luisa Nicastro; Marco Arculeo; Rosa Alduina; Antonella Costa (MDPI AG, 2021)
Arcobacter spp. are emerging waterborne and foodborne zoonotic pathogens responsible for gastroenteritis in humans. In this work, we evaluated the occurrence and the antimicrobial resistance profile of Arcobacter isolates recovered from different aquatic sources. Besides, we searched for Arcobacter spp. in seaweeds and the corresponding seawater samples. Bacteriological and molecular methods applied to 100 samples led to the isolation of 28 Arcobacter isolates from 27 samples. The highest prevalence was detected in rivers followed by artificial ponds, streams, well waters, and spring waters. Seaweeds contained a higher percentage of Arcobacter than the corresponding seawater samples. The isolates were identified as Arcobacter butzleri (96.4%) and Arcobacter cryaerophilus (3.6%). All the isolates showed a multi-drug resistance profile, being resistant to at least three different classes of antibiotics. Molecular analysis of genetic determinants responsible for tetracycline resistance in nine randomly chosen isolates revealed the presence of tetO and/or tetW. This work confirms the occurrence and the continuous emergence of antibiotic-resistant Arcobacter strains in environmental samples; also, the presence of quinolone-resistant Arcobacter spp. in aquatic sources used for water supply and irrigation represents a potential risk for human health.